PENGARUH KEPEMILIKAN INSTITUSIONAL DAN KEPEMILIKAN MANAJERIAL TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI 2012-2015 - WIDYA WULANDARI, EKA (Jurnal Akuntansi AKUNESA, 2016)
Abstract This research generally have a purpose to analyze the influence of good corporate governance mechanism that is managerial ownership and institutional ownership of the earnings management practices. In this study, researchers are expected to obtain empirical evidence that managerial and institutional ownership have a relationship on earnings management in companies listed on the Indonesian Stock Exchange (BEI) 2012-2015. In this using 50 companies selected using the method. in this study the data were analyzed using multiple linear regression, whereas  hypothesis test uses regression coefficient test, F test and t test. Results obtained from testing in this study demonstrate managerial ownership and institutional ownership has no significant effect on earnings management. This indicates that the high and low levels of ownership of the shares owned by the management and institutions can not reduce their earnings management actions within a company.  Keywords: earnings management, managerial ownership, and institutional ownership